ЗАСТОСУВАННЯ ДИНАМІЧНОГО ПРОГРАМУВАННЯ ДЛЯ ЗАДАЧІ РІВНОМІРНОГО ВИКОРИСТАННЯ ВІТРОВИХ ЕЛЕКТРОУСТАНОВОК - Медиковський , M.О.; Теслюк, В.М.; Шуневич , О.Б. (Інститут електродинаміки НАН України, Київ, 2014)
Developed the method for determining required and possible set of enabled wind turbines in real time. By means of computer simulation the examination of the uniformity of windmills’ (wind plants) wear has been realized. The behaviour of the studied system in time by means of the discrete-event simulation has been reproduced, as a result of what the determination of wind power station’s structure has been realized a fixed number of times. The results of each experiment were recorded in a data set, and then the evaluation of these experiments’ sets was carried out. References 4, figures 4.